Fatigue in intensive care survivors one year after discharge. Issue 1 (December 2016) - Spadaro, Savino; Capuzzo, Maurizia; Valpiani, Giorgia; Bertacchini, Sara; Ragazzi, Riccardo; Dalla Corte, Francesca; Terranova, Simona; Marangoni, Elisabetta; Volta, Carlo
Abstract Background Fatigue has not been investigated in long-term Intensive Care Unit (ICU) survivors. This study aimed to assess fatigue through a specific instrument, namely the Functional Assessment of Chronic Illness Therapy Fatigue (FACIT-F) scale, in ICU survivors one year after hospital discharge. A secondary aim was to compare the findings of FACIT-F with those of the Vitality domain (VT) of the 36-item Short-Form Health Survey (SF-36). Methods This prospective cohort study was performed on 56 adult patients with a Length Of Stay (LOS) in ICU longer than 72 h. At one year after hospital discharge, FACIT-F and SF-36 questionnaires were administered to consenting patients by direct interview. FACIT-F was measured as raw (range 0–52), and FACIT-F-trans value (range 0–100). Past medical history, and demographic and clinical ICU-related variables were collected. Results The patients' median age was 67.5, Simplified Acute Physiology Score II 31, and LOS in ICU 5 days. The median raw FACIT-F of the patients was 41, and Cronbach's α was 0.937. The correlation coefficient between FACIT-F-trans and VT of SF-36 was 0.660 (p  < 0.001). Both FACIT-F and VT were related to dyspnoea scale (p  = 0.01). A Bland-Altman plot of VT vs FACIT-F-trans showed a bias of –0.8 with 95 % limits of agreement from 35.7 to –34.1. The linear regression between differences and means was 0.639, suggesting a significant proportional bias. Conclusions The 13-item FACIT-F questionnaire is valid to assess fatigue of long-term ICU survivors. VT of SF-36 relates to FACIT-F, but consists of only four items assessing two positive and two negative aspects. FACIT-F grasps the negative aspects of fatigue better than VT. Specific tools assess specific conditions better that general tools. Trial registration ClinicalTrials.gov:NCT02684877 .